Implementation of Wireless Networks in Rural Areas - Al-Khalid, Hj Othman; Khairuddin, Abdul Hamid; Liew, Jing-Hong; Wee, Alvin Yeo (Damai Sciences., 2004)
This paper firstly reviews the rural condition, especially the channels of communication. Next, it examines the advantages of applying wireless technologies in rural areas. It presents two scenarios of wireless networking, with examples of implementation in Bario. In the first scenario, a wireless local area network (LAN) is set up and connected to a wired LAN using an access point. In the second scenario, a point-to-point wireless network is set up using two wireless bridges to connect two wired LANs. Both scenarios are viable to be implemented in rural areas.